IMPROVING SPEAKING ABILITY BY USING SHORT MOVIES AT ELEVENTH GRADE STUDENTS OF SMA NEGERI 5 PALU - Laiya Agus; Nur Asmawati; Andi Muhammad Dakhalan (Datokarama English Education Journal, 2020)
This research focused on the application of short movies as a media in improving speaking ability at eleventh grade students of SMA Negeri 5 Palu. The researcher applied quasi experimental research design which involved two classes of students, they were experimental class and control class. The instruments of data collection were pretest and posttest. The pretest was used to measure prior knowledge of the students and the posttest was used to measure the development of the students’ knowledge after the treatment. The t-test was analyzed to compare the mean scores of both classes. There is a significant difference score of the experimental class (1940) and the control class (1490). The level of significance was set up at 0.05 with 58 degree of freedom (df=29+31-2=58). The result of data analysis indicates that tcounted(6.84) is higher than ttable (2.002). It means that the hypothesis is accepted. Thus, the use of short movies can improve students’ speaking ability at eleventh grade students of SMA Negeri 5 Palu.